Empirical Study of Social Budget And Regional Wealth In Achieving SDG 1 (No Poverty) in Indonesia - Nur Triany Rais; Andi Chairil Furqan; Betty; Ernawaty Usman (Owner : Riset dan Jurnal Akuntansi, 2025)
This study attempts to explore the influence of social budget and regional wealth on the achievement of Sustainable Development Goals (SDGs) 1 “No Poverty” in Indonesia, which is an important issue considering the high poverty rate and the suboptimal utilization of regional budgets and wealth. This study uses secondary data from local governments in Indonesia in 2018–2022 with a total sample of 2.320 observations, and is analyzed using a panel data regression model with the Random Effect Generalized Least Squares (GLS) regression approach. The results of the study indicate that social budget and regional wealth have a significant influence on the achievement of SDGs 1. Specifically, the panel regression result show that social budgets and Regional Government Expenditure (APBD) are significant at the 1% level with an Adjusted R2 of 0,147. By increasing the allocation of social budgets and managing and utilizing regional wealth optimally, local governments can carry out poverty alleviation efforts more effectively, accelerate poverty reduction, and aid in the region’s attainment of Sustainable Development Goals. This study emphasizes the importance of local governments to increase targeted social budget allocations, manage regional wealth more productively, and design policies that focus on sustainable poverty reduction to support the achievement of SDGs 1 targets.